Assessing waste management performance in smart cities through the ‘Zero Waste Index’: case of African Waste Reclaimers Organisation, Johannesburg, South Africa - Siwawa, Vincent (Frontiers in Sustainable Cities, 2025)
The study investigates waste management performance in Johannesburg, South Africa, focusing on the African Waste Reclaimers Organisation (ARO) within the smart city framework and using the ‘Zero Waste Index.’ Addressing the challenges of waste management in the Global South, this study evaluates ARO’s strategies and the impact of digital technologies on waste diversion practices. A mixed-methods approach was employed, incorporating quantitative data from ARO’s annual and monthly waste category records (received via email in 2022) and qualitative insights gathered through direct involvement and participation in the BanQu Project and municipal databases. Data sources were selected based on relevance, reliability, and availability of comprehensive waste management statistics. Key stakeholders, including waste pickers, policymakers, and community members, were considered through documented records from ARO’s waste management programs, municipal and government reports. The study found that approximately 9.21% of Johannesburg’s total waste is diverted from landfills, with a ‘Zero Waste Index’ of 0.34, indicating that 33.82% of resources are reclaimed. Analysis of resource substitution values for various waste categories demonstrated the significant contributions of waste reclaimers to material substitution and environmental conservation. The study reveals that digital technologies, such as ICT-enabled platforms and blockchain, play a crucial role in optimising waste diversion practices. These technologies facilitate real-time monitoring, data collection, and transparent transactions, enhancing the efficiency of waste reclaimers and contributing to improved environmental outcomes. Additionally, the research emphasises the importance of integrating informal waste pickers into formal waste management systems to maximise resource recovery and sustainability, recommending innovative policies, public awareness campaigns, and collaborative efforts among stakeholders to achieve zero-waste goals. Johannesburg’s commitment to comprehensive waste management strategies, evident in its ‘Zero Waste Index,’ positions waste reclaimers as leaders in urban sustainability and environmental responsibility, setting a benchmark for other cities aiming for zero-waste objectives.